Inovasi Pengembangan Film Dokumenter Sinematografi Sebagai Upaya Akselerasi Aset Digital Marketing Industri Tape Desa Banjarsari - Iriaji; Abdul Rahman Prasetyo; Agusta Rakhmat Taufani; Alby Aruna; Eka Putri Surya; Ginanjar Atma Wijaya; Adinda Marcelliantika (Sci-tech Journal, 2024)
The development of innovations in the production of cinematographic documentaries aims to accelerate digital marketing assets for the tape industry in Banjarsari Village. Through a methodology that includes analyzing digital marketing needs, designing documentary concepts, and evaluating the effectiveness of marketing campaigns, the documentary is designed to showcase the tape-making process in depth and engaging, as well as promote local cultural values. A significant increase in brand awareness and consumer interest in tape products from Banjarsari Village was revealed from the results of this activity. Evaluations conducted through in-depth surveys and interviews confirm the effectiveness of this approach in supporting digital marketing strategies and expanding market reach. The innovations applied in this cinematographic documentary not only increase consumer interest but also play an important role in strengthening marketing strategies and expanding market reach through an engaging visual approach. Thus, an important contribution is made to the development of innovative digital marketing assets for the rural tape industry, demonstrating that this approach is effective in supporting digital marketing strategies as well as expanding the market and increasing brand awareness of local products.